Effect of prone positioning for improving oxygenation in awake non-intubated COVID-19 patient: a systematic review - I Made Yoga Prabawa; Dedi Silakarma; Sisca Susantio (DiscoverSys Inc., 2021)
Background. The rapid rise of COVID-19 cases in many regions impacted on increasing needs of intensive care units and oxygen supplementation. The exponential COVID-19 infection with moderate to severe hypoxia that needs oxygen supplementation causes medical oxygen shortage in most hospitals and swamped the health care system. Prone positioning can be an alternate way for non-hospitalized COVID-19 patients, especially in the region facing oxygen and ward shortage in hospitals. This systematic review will describe the impact of the prone positioning method for improving oxygenation in awake non-intubated COVID-19 patients.Method. A systematic review using PubMed and Google Scholar was conducted based on PRISMA guidelines. We used inclusion criteria such as observational study with cross sectional, cohort, case-control or clinical trial study design regarding the effect of prone positioning for improving oxygenation in COVID-19 patients. Exclusion criteria were a letter to the editor, commentary reports, systematic review or meta-analysis, study involving non-awake and or intubated patients and study not available in full-text. Result. We gathered eleven studies consisting of six retrospective observational studies, three prospective observational studies and two clinical trials comprised of one randomized controlled trial and one interventional study. There are 791 awake non-intubated COVID-19 patients as the study sample. The measured outcomes are changes in SaO2, P/F ratio, S/F ratio, ROX index, intubation and mortality rate. The prone positioning duration varies between 29 minutes until 12 hours and helps improve oxygenation, reducing intubation and mortality. Conclusion. Prone positioning is feasible to apply in awake non-intubated COVID-19 patients. It can improve oxygenation, reduce intubation, mortality rate and be beneficial to overcome oxygen and mechanical intubation shortage during the COVID-19 pandemic.